1991
DOI: 10.1002/cjce.5450690414
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism, onset and intensity of surface aeration in geometrically‐similar, sparged, agitated vessels

Abstract: Under sparged conditions surface aeration occurs by two mechanisms: first, the absorption of gas at the free surface and then its desorption at the gas bubbles‐liquid interfaces, and second, mechanical suction through the free surface; the latter is believed to occur via vortices formed on the free surface due to impeller action. The onset of gas entrainment is defined through the characteristic impeller speed above which mechanical suction rapidly increases. Gas entrainment intensity is correlated by the spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…It was found that the creation of a vortex, which is advantageous for drawing down the floating solids, is not easy under aerated conditions (Bakker and Frijlink, 1989). Veljkovic et al (1991) …”
Section: Comparison With Literaturementioning
confidence: 97%
“…It was found that the creation of a vortex, which is advantageous for drawing down the floating solids, is not easy under aerated conditions (Bakker and Frijlink, 1989). Veljkovic et al (1991) …”
Section: Comparison With Literaturementioning
confidence: 97%
“…The mass transfer coefficients of the multiple impeller system reported by Matsumura et al (1982b) appears to be superior as compared to the other designs. Wu (1995) has shown that submergence is an important parameter, and mass transfer coefficient decreases rapidly with an increase in the submergence. 5.…”
Section: Discussionmentioning
confidence: 98%
“…Whereas, the PdP, ratio for the bottom impeller was correlated with the aeration number. Wu (1995) has shown that, for a disc turbine located very close to the free liquid surface, the power number could be correlated with the Froude number. He has also shown that there was no effect of tank diameter on the power consumption.…”
Section: Power Consumptionmentioning
confidence: 97%
See 2 more Smart Citations